Improving melanoma screening in primary care: the Experience of the Association of French General Practitioners Practicing Dermoscopy - Julien Anriot; Nadia Ikhlef; Gérard Duru; Sophie Darnis; Pauline Scouarnec; Younes Tamarat; Amini-Adle Mona; Luc Thomas (Dermatology Practical & Conceptual)
Background: Melanoma constitutes an increasing global health burden. In the light of a growing shortage of dermatologists in several countries, primary care has emerged as an optimal setting for skin cancer screening. Historically, in France, skin cancer detection was typically managed by dermatologists, while general practitioners (GPs) were barely involved. In 2021, the Association of French GPs practicing Dermoscopy was created to address this gap by promoting and legitimizing dermoscopy practice among primary care physicians.